Both Microtubule-Stabilizing and Microtubule-Destabilizing Drugs Inhibit Hypoxia-Inducible Factor-1α Accumulation and Activity by Disrupting Microtubule Function - Escuin, Daniel (Cancer Res, 2005)
We have recently identified a mechanistic link between disruption of the microtubule cytoskeleton and inhibition of tumor angiogenesis via the hypoxia-inducible factor-1 (HIF-1) pathway. Based on this model, we hypothesized that other microtubule-targeting drugs may have a similar effect on HIF-1α. To test that hypothesis, we studied the effects of different clinically relevant microtubule-disrupting agents, including taxotere, epothilone B, discodermolide, vincristine, 2-methox-yestradiol, and colchicine. In all cases, HIF-1α protein, but not mRNA, was down-regulated in a drug dose–dependent manner. In addition, HIF-1α transcriptional activity was also inhibited by all drugs tested. To further examine whether these effects were dependent on microtubule network disruption, we tested the ability of epothilone B to inhibit HIF-1α protein in the human ovarian cancer cell line 1A9 and its (β-tubulin mutant epothilone-resistant subclone 1A9/A8. Our data showed that epothilone B treatment down-regulated HIF-1α protein in the parental 1A9 cells but had no effect in the resistant 1A9/A8 cells. These observations were confirmed by confocal microscopy, which showed impaired nuclear accumulation of HIF-1α in parental 1A9 cells at epothilone B concentrations that induced extensive microtubule stabilization. In contrast, epothilone B treatment had no effect on either microtubules or HIF-1α nuclear accumulation in the resistant 1A9/A8 cells. Furthermore, epothilone B inhibited HIF-1 transcriptional activity in 1A9 cells, as evidenced by a hypoxia response element-luciferase reporter assay, but had no effect on HIF-1 activity in the resistant 1A9/A8 cells. These data directly link β-tubulin drug binding with HIF-1α protein inhibition. Our results further provide a strong rationale for testing taxanes and epothilones in clinical trials targeting HIF-1 in cancer patients.